2019
DOI: 10.1002/celc.201900817
|View full text |Cite
|
Sign up to set email alerts
|

S−ZnO/CNTs Microspheres Prepared by Spray Drying for Improved Cathodes in Lithium‐Sulfur Batteries

Abstract: In this work, S−ZnO/CNTs microspheres were prepared by spray drying to yield caddice‐like ball morphologies, composed of large numbers of carbon nanotubes deposited with ZnO nanoparticles. This synthesis route was advantageous since sulfur was loaded simultaneously and caddice‐like ball morphologies were formed in one step during spray drying. The unique hierarchical structure and polycrystalline nature of S−ZnO/CNTs microspheres did not only facilitate the physical and chemical confinement of sulfur but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The chemical composition of the resulting Al-MOG@S-RGO was investigated by XPS elemental analysis measurement, and the results are provided in Figure c–e. The spectrum of S 2p in Figure c revealed three contributions, S 2p 3/2 and S 2p 1/2 for S 8 molecule and CS bond, present at 163.8, 164.8, and 168.5 eV, respectively. , The binding energy peak strength ratio of S 2p 3/2 and S 2p 1/2 is 2:1, which corresponds well with the characteristics of solid sulfur in the materials. The CS peak can be assigned to the coaction of surface sulfur with carbon.…”
Section: Resultsmentioning
confidence: 53%
“…The chemical composition of the resulting Al-MOG@S-RGO was investigated by XPS elemental analysis measurement, and the results are provided in Figure c–e. The spectrum of S 2p in Figure c revealed three contributions, S 2p 3/2 and S 2p 1/2 for S 8 molecule and CS bond, present at 163.8, 164.8, and 168.5 eV, respectively. , The binding energy peak strength ratio of S 2p 3/2 and S 2p 1/2 is 2:1, which corresponds well with the characteristics of solid sulfur in the materials. The CS peak can be assigned to the coaction of surface sulfur with carbon.…”
Section: Resultsmentioning
confidence: 53%
“…However, C scaffolds can only confine polysulfides physically because of the weak nonpolar interaction between polysulfides and C. 20 Many efforts have been devoted to exploring highly conductive S hosts combined with polarity. Recent research studies have demonstrated that coupling C scaffolds with metal oxides/sulfides, such as ZnO, 21 V 2 O 5 , 22 ZnS, 7 and CoS 2 , 23 can effectively chemisorb polysulfides and mitigate the shuttle effect. These approaches do improve the capacity and cycling stability of LSBs.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the polar LiPSs cannot be effectively confined into the pore structure of these nonpolar carbon host materials due to the weak interactions, resulting in low coulombic efficiency and rapid capacity degradation. [11,12] Polarization treatments of carbon-based host materials by introducing heteroatoms, [13][14][15][16] or transition metal compounds [17][18][19][20][21] have been adopted to enhance the confinement of LiPSs. Admittedly, these treatments can effectively inhibit the shuttle effect for LSBs with a low sulfur content by simultaneously chemically trapping LiPSs and improving the corresponding redox reactions.…”
Section: Introductionmentioning
confidence: 99%